Effects of Slaughter Weight and Muscle Types on Carcass and Meat Quality Characteristics of Holstein Friesian Bulls - Kocyigit, R; Yanar, M; Özdemir, VF; Aydin, R; Diler, A (Journal of the Hellenic Veterinary Medical Society, 2024)
The aim of this study was to determine the effects of slaughter weight and muscle types on carcass characteristics, chemical composition and meat quality characteristics of young Holstein Friesian bulls. For this purpose, the 21 young bulls were assigned to three experimental groups based on their weights at slaughter called lighter (LSW) (470.4±32.5kg), medium (MSW) (540.8±10.9 kg) and heavier (HSW) (605.8±28.3 kg). Animals in the HSW group resulted in higher carcass weight, LD area, crude protein content, pH24 value. On the other hand, L* and a* values color parameters and LD area per 100 kg carcass weight were significantly decreased with the increasing slaughter weight. The meat obtained from the LSW group were brighter and redder compared to other two slaughter groups. Additionally, there was a decreasing trend in the proportion of the non-carcass components with increasing of the slaughter weight. However, increasing of the slaughter weights led to a significant increase in the carcass measurements such as thoracic depth, carcass length, length of the round as well as width of the round. Although the crude protein content was significantly affected by both slaughter weights and muscle types, only muscle types were also significant sources of variation in percentages of moisture and crude ash.